लोकतत्त्व र तेस्रो लिङ्‍गीकोदृष्टिले लगन उपन्यासको अध्ययन - Pradhan, Suchan (Haimaprabha, 2025)
“Lagan” Achcha Rai Rasik’s first novel, depicts various dimensions of society, especially folk life, social values, caste, the context of women’s education, and the complexities of love relationships. Especially a glimpse of rural and urban life in Darjeeling and its surroundings is found in it. Saturday markets, caste discrimination, poverty, cultural activities, religious beliefs, ethnic discrimination, traditional beliefs, and economic conditions are realistically depicted. Various folk beliefs existing in Nepali society such as screaming foxes, blinking eyes, turning off lights, and funeral rites of the deceased are mentioned in the novel. These beliefs seem to have had a deep impact on folk culture. Judging from the current research techniques, there is no direct mention of the third gender community in the novel. However, the gender roles, female education, and the structure of a patriarchal society depicted in the novel also make the context of gender diversity and identity reflective. The characters in the novel rebel against the gender and caste discrimination, which represents a consciousness that stands against traditional thinking. Various aspects of folk life, traditional thinking, caste discrimination, folk beliefs, issues of women’s education, and the complexities of love are at the center of the novel. From a contemporary perspective, the novel shows the need for in-depth study in the context of gender equality and diversity. An attempt has been made to shed light on these issues in the present article.